Portraits of the garçonne as artist: gender and creativity in French fiction of the années folles - Shingler, Katherine (Routledge, 2018)
This article examines a series of popular and middlebrow works of fiction from the 1920s which represent the garçonne (the flapper, or androgynous, emancipated young woman) as artist. Challenging the popular view of the années folles as a period of relatively relaxed social conventions and gender norms, it shows that far from embracing female creativity, the authors of the period took pains to link it to moral and aesthetic deviance. Having considered what the representation of female creativity in novels by Berthe Bernage, Victor Margueritte and Marcel Prévost can tell us about gender in the 1920s, I go on to examine novels by the art critics André Warnod and François Fosca, who use the figure of the garçonne as artist to air art-critical positions about the modernist art produced in Montparnasse, especially by members of the École de Paris. Whereas Warnod represents his female artist as a victim of a modernism linked with the foreign and the ‘primitive’, in Fosca’s novel the female painter is a more threatening figure: an agent of a modernism whose attacks on the female body (in the form of the conventional academic nude) are in turn echoed in a broader ‘troubling’ of gendered and aesthetic categories.